Pelaksanaan Peraturan Daerah Di Era Otonomi Daerah Di Kabupaten Nganjuk - Ahmad Sholikhin Ruslie (Fakultas Hukum Universitas Darul Ulum, 2015)
The problem in this research is how the local government according to Law number 22 of 1999.?. With the aim of research to find out what regional regulations have been issued by the district government. With diskriptid qualitative research methods and the acquisition of data on primary data sourced from literature and field data.The results were obtained under unfounded OTDA number 22 of 1999, the government issued a lot PERDA Kediri in PERDA no. 9 of 2000 which establishes the Office 15, Office 8, 3 Agency, 21 districts, 4 Village, DPRD Secretariat, the Regional Secretariat with 4 Assistants and 10 Section.